TABLETS. REGULATORY REQUIREMENTS OF THE STATE PHARMACOPOEIA XIII EDITION - N. V. Isaeva; A. I. Tulaykin; E. V. Sheshegova (Разработка и регистрация лекарственных средств, 2019)
Comparative analysis of pharmacopoeial requirements for dosage forms tablets has been made due to the introduction of the State Pharmacopoeia of the Russian Federation XIII edition. An overview of changed requirements can be useful for revision (reissue) of monographs and normative documentation for tablets.